Nonclinical Safety Assessment of CFZ533, a Fc-Silent Anti-CD40 Antibody, in Cynomolgus Monkeys. (7th August 2018) - Ulrich, Peter; Flandre, Thierry; Espie, Pascal; Sickert, Denise; Rubic-Schneider, Tina; Shaw, David A; Rush, James S
Abstract: CFZ533 is a pathway blocking, nondepleting anti-CD40 antibody that is in clinical development for inhibition of transplant organ rejection and therapy for autoimmune diseases. A 26-week GLP toxicity study in sexually mature Cynomolgus monkeys was conducted in order to support chronic application of CFZ533. CFZ533 was subcutaneously administered at doses up to 150 mg/kg/week and was safe and generally well tolerated. CFZ533 showed no adverse effects for cardiovascular, respiratory, and neurobehavioral endpoints, and no changes were observed for blood lymphocyte and platelet counts or blood coagulation markers. In line with the nondepleting nature of CFZ533, CD20 + B cells in the blood were only marginally reduced. A complete suppression of germinal center (GC) development in lymph nodes and spleen was the most prominent result of post-mortem histological investigations. This was corroborated by an abrogated T-dependent antibody response (TDAR) to the antigen Keyhole Limpet Hemocyanin (KLH) as well as an absence of anti-drug antibodies (ADAs) in the absence of B cell depletion as seen with immunophenotyping and histology. When serum levels of CFZ533 in recovery animals dropped levels necessary for full CD40 occupancy on B cells, all animals were able to mount a TDAR to KLH. All histological changes also reverted to normal appearance after recovery. In summary, CFZ533 was shown to be well tolerated and safe in the 26-week toxicity study with a distinct pharmacodynamic profile in histology and immune function.